Peningkatan Prestasi Belajar PAI Materi Wudhu Melalui Metode Demonstrasi Pada Siswa Kelas IV Di UPT SDN 05 Nanggalo - Saputra, Hamdani (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes on the topic of wudhu steps in the 4th-grade class of SD Negeri 05 Nanggalo by applying the Demonstration method. The research uses a Classroom Action Research (CAR) approach with two cycles. In the first cycle, students’ learning outcomes were low, with only 27% of students reaching the Minimum Completeness Criteria (KKM). However, after applying the Demonstration method in the second cycle, all students achieved passing grades. The Demonstration method proved effective in enhancing students’ understanding, their engagement in learning, and boosting their motivation. Based on these results, it is recommended to apply the Demonstration method in Islamic Religious Education to improve students’ learning outcomes.